IMPROVING READINGCOMPREHENSION THROUGH ‘GETTINGTHE FACT TECHNIQUE’ - Mangiri, Riche; Bunau, Eusabinus; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract:This thesis is entitled Improving Reading Comprehension Through ?Getting The Fact Technique? (A Classroom Action Research to Year-10 Students of SMAK AbdiWacana Pontianak in Academic Year 2015/2016). It is aimed to find out the the answer of research questions, those are: (1) How can Getting the Fact Technique (GFT) improve reading comprehension to Year-10 students of SMAK AbdiWacana Pontianak in Academic Year 2015/2016? (2) What problems are encountered by Year-10 students of SMAK AbdiWacana Pontianak in Academic Year 2015/2016 when they are taught using Getting the Fact Technique (GFT)? The type of research applied to this research was Classroom Action Research (CAR) that was implemented in two cycles, The average score of students? test was 78.52 with the qualification of ?average to good? in cycle one and 87.48 with the qualification of ?good to excellent? in cycle two. It means that the average score of the tests on the material taught using FGT technique was higher than the minimum achievement criterion for English subject accomplishment for year-10 of SMAK Abdi Wacana Pontianak, that is 65.     Keywords: Reading Comprehension, Getting the Fact Technique Abstract: Tujuan dari penelitian ini adalah Meningkatkan Komprehensi Membaca Melalui Teknik ?Getting The Fact?( Suatu Penelitian Tindakan Kelas Pada Siswa Kelas 10 SMAK Abdi Wacana Pontianak Tahun Pelajaran 2015/2016. Bagaimanakah Teknik ?Getting The Fact? dapat meningkatkan komprehensi membaca pada siswa kelas 10 SMAK Abdi Wacana Pontianak tahun pelajaran 2015/2016? Masalah-masalah apa sajakah yang dihadapi oleh siswa kelas 10 SMAK Abdi Wacana Pontianak tahun pelajaran 2015/2016 ketika diajarkan melalui teknik ?Getting the Fact?? Jenis penelitian ini adalah penelitian Tindakan kelas (PTK) yang dilaksanakan dalam dua siklus, Nilai rata-rata tes siswa adalah 78,52 dengan kategori ?average to good? pada siklus 1 dan 87,48 dengan kategori ?good to excellent? pada siklus 2. Hal itu menunjukkan bahwa nilai rata-rata hasil tes formatif dari materi yang diajarkan melalui teknik ?Getting The Fact? lebih tinggi dibandingkan dengan nilai KKM Kelas 10 SMAK Abdi Wacana Pontianak, yaitu 65.   Kata Kunci: Komprehensi Membaca,Teknik ?Getting the Fact?